ANALISIS KAPASITAS RUNWAY BANDARA I GUSTI NGURAH RAI MENGGUNAKAN TEORI ANTREAN - RUKITO, KHOSYI; SUMARJAYA, I WAYAN; SRINADI, I GUSTI AYU MADE (E-Jurnal Matematika; Vol 8 No 3 (2019)DO - 10.24843/MTK.2019.v08.i03.p258, 2019)
Bali, as one of the world's tourism destination, located separately from other islands in Indonesia. Many tourists travel to Bali by airplane, and I Gusti Ngurah Rai Airport is the only international airport that serves as the main gate to Bali. There are situations in which the airport's runway often has to deal with an extensive queue for both landing and departure, which results in flight delays. Flight delays have caused some problems such as ruin airlines reputation and decline demand by passangers. The aim of the research is to analyze the efficiency of I Gusti Ngurah Rai International Airport's runway so the airport service can be optimized using queueing theory. In this research, there were four categories used: the high season in July 2018, the special event Annual Meeting International Monetary Fund-World Bank in October 2018, the low season in February 2019, and the overall data. In this research, it was found that the model used in this airport’s runway is (M/G/I):(FIFO/?/?). This model is not in a steady-state condition, with the level of bustle approximately around 177% until 191%. Therefore, an additional runway is recommended and also the runway service needs to be accelerated for optimal condition.